Curriculum and Teaching Dialogue. Vol 16, issue 1 & 2 - Flinders, David J.; Uhrmacher, P. Bruce; Moroye, Christy M. (Curriculum & teaching dialogue, 2014)
Curriculum and Teaching Dialogue (CTD) is a publication of the American Association of Teaching and Curriculum (AATC), a national learned society for the scholarly fields of teaching and curriculum. The fields includes those working on the theory, design and evaluation of educational programs at large. University faculty members identified with this field are typically affiliated with the departments of curriculum and instruction, teacher education, educational foundations, elementary education, secondary education, and higher education.CTD promotes all analytical and interpretive approaches that are appropriate for the scholarly study of teaching and curriculum. In fulfillment of this mission, CTD addresses a range of issues across the broad fields of educational research and policy for all grade levels and types of educational programs.